2022
DOI: 10.1007/s40831-022-00526-8
|View full text |Cite
|
Sign up to set email alerts
|

Wettable TiB2 Cathode for Aluminum Electrolysis: A Review

Abstract: Titanium diboride (TiB2) is considered a promising material for wettable cathodes in aluminum electrolysis. The demand for wettable cathodes is associated with the development of inert anode technologies to eliminate CO2 emissions caused by the conventional aluminum reduction process. Titanium diboride has been given special attention due to its superior properties, such as high wettability, good electrical conductivity, wear resistance, and excellent chemical stability. In this paper, we discuss different syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Taking into account the above results and discussion, the scheme of the anode process on Pt in KF-AlF 3 -Al 2 O 3 melts includes chemical equilibrium (9) and below reactions:…”
Section: Comentioning
confidence: 97%
See 1 more Smart Citation
“…Taking into account the above results and discussion, the scheme of the anode process on Pt in KF-AlF 3 -Al 2 O 3 melts includes chemical equilibrium (9) and below reactions:…”
Section: Comentioning
confidence: 97%
“…[1][2][3] Significant progress has been made in the field of creating oxygen-evolving anodes and aluminum-wetted cathodes over the past two decades. [4][5][6][7][8][9] However, even the most corrosion-resistant materials cannot withstand the simultaneous effects of high temperature and aggressive electrolyte. The situation changes when the cryolite-alumina melt is replaced with a KF-AlF 3 -Al 2 O 3 based molten electrolyte offering an operating temperature in the range of 750 °C-850 °C.…”
mentioning
confidence: 99%
“…And titanium diboride is considered a promising material for wettable cathodes in aluminum electrolysis. 65,125 Yang et al studied the wettability of coating in molten aluminum electrolysis system and found that the wettability of TiB 2 coating and aluminum liquid was better than that of graphite cathode carbon block and aluminum liquid. 126 The better the molten salt wets the material, the greater the critical current density.…”
Section: Ionic Radiusmentioning
confidence: 99%
“…123 The wetting of TiB 2 by Al liquid depends on the relative density and purity of TiB 2 material and interaction temperature. 7 Heidari et al reported that the aluminium wettability of TiB 2 is proportional to the interaction temperature. 124 At 870 °C under vacuum, no visible wetting of TiB 2 by Al was observed.…”
Section: Tib 2 Based Cathodesmentioning
confidence: 99%
“…As TiB 2 is deemed highly expensive, trials have been made to use TiB 2 coatings on various substrates to examine the adhesiveness of the TiB 2 layer. 7 This paper summarises the developments in inert anodes technology and will discuss anode materials such as metals, ceramics and cermets. A brief discussion will be provided on low-temperature electrolytes potentially used in aluminium electrolysis and their properties, such as electrical conductivity and alumina solubility.…”
mentioning
confidence: 99%